2021
DOI: 10.3390/nu13030973
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Micronutrient Intake, Sociodemographic, and Behavioral Factors on Periodontal Status of Adults Assisted by a Public Health Care System in Brazil: A Cross-Sectional Multivariate Analysis

Abstract: The lack of access to a balanced diet, rich in vitamins and minerals, can predispose people to inflammatory diseases such as obesity, diabetes mellitus, and periodontitis. We aimed to evaluate the relationship between micronutrient intake, sociodemographic behavioral characteristics, and periodontal health in adults assisted by a public health care system. Participants (n = 450) answered a food frequency questionnaire and were submitted to anthropometric and oral clinical examinations. Principal component anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 92 publications
(111 reference statements)
0
11
0
Order By: Relevance
“…The dietary record was evaluated for the intake of the following nutrients as described previously [ 40 ]: omega-3, omega-6, fiber, calcium (Ca), magnesium (Mg), manganese (Mn), phosphorus (P), iron (Fe), sodium (Na), potassium (K), copper (Cu), zinc (Zn), vitamin A (retinol), thiamine, riboflavin, pyridoxine, niacin and vitamin C. In addition to these, the intake of macronutrients such as carbohydrates, proteins and lipids was quantified and associated with the respective energy content. For the estimation of dietary consumption of nutrients, we used a conversion table (TACO table) [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The dietary record was evaluated for the intake of the following nutrients as described previously [ 40 ]: omega-3, omega-6, fiber, calcium (Ca), magnesium (Mg), manganese (Mn), phosphorus (P), iron (Fe), sodium (Na), potassium (K), copper (Cu), zinc (Zn), vitamin A (retinol), thiamine, riboflavin, pyridoxine, niacin and vitamin C. In addition to these, the intake of macronutrients such as carbohydrates, proteins and lipids was quantified and associated with the respective energy content. For the estimation of dietary consumption of nutrients, we used a conversion table (TACO table) [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…The sociodemographic and clinical characteristics evaluated were age, sex, educational level, income, physical activity frequency, smoking, consumption of alcoholic beverages and the presence of CNCDs (diabetes mellitus, hypertension, hypercholesterolemia, hypertriglyceridemia, hypothyroidism, liver steatosis, cardiopathy, cancer history, depression). Some of these variables were dichotomized, namely educational level ≥8 years of study, smoking yes or no and family income up to two minimum wages or higher (approximately USD 500) [ 40 ] ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These include genetic 10 and epigenetic influences, 11 medication use 12 and/or environmental factors, 13 which together promote periodontal disease initiation and progression. Low socioeconomic status, poor oral hygiene, and oral health related behaviors, psychological stress, and/or depression, increased age, ethnicity, diet/obesity, and systemic health comorbidities are risk factors that contribute to the prevalence of periodontal diseases 14,15 . Large epidemiological studies have shown a relationship between periodontal disease and some systemic conditions.…”
Section: Introductionmentioning
confidence: 99%